Ghosts : a nonfiction companion to a good night for ghosts - Osborne, Mary Pope (Magic tree house research guide., 2009)
A guide to ghosts discusses the history of human belief in them, famous hauntings in the United States and Great Britain, and some possible alternative explanations for them.